V-b composite microalloyed spring steel wire rod without full decarburized layer and its production method
Patent Information
- Application Number
- CN202611206936.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-13
AI Technical Summary
[0009]为了克服现有技术的不足,本发明提供一种消除全脱碳层的V-B复合微合金化弹簧钢盘条及其生产方法,旨在解决现有55SiCr弹簧钢盘条生产过程中表面全脱碳层难以消除、总脱碳层深度超标的问题
1.成分设计与工艺控制的协同作用实现了脱碳层的有效控制
Smart Images

Figure CN122898804A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of steel material preparation, specifically to a VB composite microalloyed spring steel wire rod with a completely decarburized layer and its production method. Background Technology
[0002] 55SiCr spring steel is a core material for automotive suspension systems and shock absorbers. Its mechanical properties, microstructure uniformity, and surface quality directly determine the fatigue life of the spring and the operational safety of the components. Due to its moderate carbon content and reasonable alloy system, 55SiCr spring steel achieves a good balance between strength, toughness, hardenability, and fatigue performance, making it the preferred steel for suspension springs in mid-to-high-end passenger and commercial vehicles both domestically and internationally. It is widely used in the manufacture of elastic components requiring high stress and long fatigue life.
[0003] In the industrial production of 55SiCr spring steel wire rod, the hot rolling process involves multiple steps, including high-temperature heating and holding, continuous rolling, and controlled cooling during wire drawing. Under high-temperature conditions, the steel billet reacts with the furnace atmosphere, causing surface carbon atoms to diffuse and escape into the atmosphere, easily forming a significant decarburized layer, including both fully and partially decarburized layers. This decarburized layer significantly reduces the surface hardness and fatigue performance of the steel, and can lead to surface cracks during subsequent drawing processes, spring failure, or early fatigue fracture during service, severely impacting safety.
[0004] In response to the decarburization problem of spring steel, the industry has conducted extensive research and proposed a variety of control solutions.
[0005] Chinese patent document CN1279204C discloses "a high-stress spring steel for automobiles," which improves the steel's decarburization resistance by adding trace amounts of rare earth, tungsten, and boron elements, while simultaneously reducing carbon content to improve toughness. However, this approach relies on rare earth elements, which are unevenly distributed and subject to significant price fluctuations. Furthermore, the addition of rare earth elements places high demands on smelting processes and equipment, increasing the difficulty and cost of industrial production. Additionally, this patent does not propose a systematic process control scheme for the decarburization problem of 55SiCr steel.
[0006] Chinese patent document CN115870332A discloses a "production method for eliminating complete decarburization of Si-Cr spring steel wire rod while improving fatigue life," which suppresses decarburization by spraying an anti-decarburization coating onto the surface of a hot continuously cast billet, combined with a multi-stage heating regime and post-rolling controlled cooling process. However, this method relies on specialized spraying equipment and coating formulations, and the coating is prone to scraping and peeling off during billet transportation and furnace loading, leading to localized failure of the anti-decarburization effect. Furthermore, this method does not reduce the decarburization sensitivity of the material at the level of steel chemical composition design, and it is difficult to achieve stable elimination of the completely decarburized layer by relying solely on physical isolation and process control.
[0007] Chinese patent document CN116445698A discloses a "complete decarburization control process for 55SiCr automotive spring steel wire rod," which eliminates the decarburized layer by peeling and rounding the corners of the steel billet, combined with a three-stage heating system (preheating, heating, and soaking) and cooling rolling after exiting the furnace. However, this solution requires peeling the steel billet, increasing the number of processes and costs. Furthermore, the peeling process requires high operational precision, and defects such as steps and burrs on the billet surface are easily generated, potentially becoming new crack sources. Simultaneously, this process mainly controls decarburization by adjusting the heating system, requiring extremely high temperature control precision in the heating furnace, and its adaptability and stability in industrial production need improvement.
[0008] In summary, the existing technologies still have the following shortcomings in controlling the decarburization of 55SiCr spring steel: (1) There are limited means of controlling the decarburization sensitivity at the composition design level, and there is a lack of effective ways to inhibit the diffusion of carbon atoms from the microscopic mechanism; (2) The process control schemes mostly rely on special equipment or complex processes, resulting in high production costs and poor industrial adaptability; (3) The existing schemes are difficult to ensure that the total decarburization layer depth meets the high standard requirements while eliminating the entire decarburization layer. Summary of the Invention
[0009] To overcome the shortcomings of existing technologies, this invention provides a VB composite microalloyed spring steel wire rod with a completely decarburized layer and its production method, aiming to solve the problems of difficulty in eliminating the completely decarburized layer and excessive total decarburized layer depth in the production of existing 55SiCr spring steel wire rods. This invention combines VB composite microalloying composition design with matched heating, rolling, and cooling process control to synergistically inhibit decarburization from both compositional and process perspectives. This achieves complete elimination of the completely decarburized layer and controls the total decarburized layer depth to below 0.5%D, while also being suitable for stable industrial production.
[0010] To achieve the above objectives, the present invention employs the following technical solution: A VB composite microalloyed spring steel wire rod with a completely decarburized layer is composed of the following chemical composition by weight percentage: C: 0.51%~0.59%, Si: 1.30%~1.50%, Mn: 0.60%~0.80%, P≤0.015%, S≤0.010%, Cr: 0.60%~0.75%, V: 0.02%~0.04%, B: 0.0005%~0.0015%, and the weight percentage ratio of V / B is 15~80, with the balance being Fe and unavoidable impurities.
[0011] The effect of selecting the above alloying elements and their contents: 1. C: Carbon is the most important strengthening element in spring steel, and its influence on the strength and plasticity of wire rod is most significant. Increasing the carbon content can effectively improve the strength level of wire rod, but excessive carbon content will drastically reduce plasticity and increase carbon activity, exacerbating the tendency of carbon atoms to diffuse to the surface during heating and rolling, thereby increasing decarburization sensitivity. This invention controls the C content at 0.51%~0.59%, which ensures the necessary strength requirements of spring steel while avoiding excessive carbon content from exacerbating the decarburization tendency, so that the wire rod achieves a good strength and toughness balance during subsequent quenching and tempering heat treatment.
[0012] 2. Si: Silicon has a significant solid solution strengthening effect, which can refine the interlamellar spacing of pearlite and improve the elastic limit, yield strength, and tempering stability of springs. Simultaneously, Si can inhibit cementite precipitation and improve the stability of austenite. However, Si is a non-carbide-forming element and can increase carbon activity; excessive addition will significantly increase the decarburization sensitivity of steel and promote the formation of a decarburized layer on the surface during heating. This invention controls the Si content at 1.30%~1.50%, which fully utilizes its beneficial effects of solid solution strengthening and inhibiting cementite precipitation while avoiding the exacerbation of decarburization due to excessive Si content.
[0013] 3. Mn: Manganese is an effective element for improving hardenability, refining the interlamellar spacing of pearlite, and increasing the strength of high-carbon steel. However, when Mn is enriched in the segregation zone of the billet, it easily produces a low-temperature structure, reducing the drawing performance and processing plasticity of the wire rod. This invention controls the Mn content at 0.60%~0.80%, ensuring hardenability and strength while avoiding the adverse effects of the low-temperature structure in the segregation zone on processing performance.
[0014] 4. Cr: Chromium can significantly improve the hardenability, high-temperature strength, and tempering stability of steel, and refine the pearlite lamellar spacing. More importantly, Cr is a moderately strong carbide-forming element, which can inhibit the continuous precipitation of grain boundary carbides, reduce carbon activity, and thus effectively reduce the decarburization sensitivity of steel. This invention controls the Cr content at 0.60%~0.75%, ensuring hardenability and tempering stability while fully leveraging its beneficial effect of inhibiting decarburization.
[0015] 5. Vanadium (V): Vanadium is a strong carbide-forming element. By forming fine vanadium (VC) carbonitrides that pin grain boundaries, it effectively refines austenite grains. Grain refinement increases the total grain boundary area, reducing the diffusion flux of carbon along grain boundaries; it also provides more effective grain boundary area for subsequent boron (B) grain boundary segregation. Simultaneously, the carbonitride precipitates of vanadium can reduce the diffusion coefficient of carbon in austenite, decreasing the migration and loss of carbon atoms to the surface, thereby reducing decarburization sensitivity from an intragranular perspective. This invention controls the vanadium content at 0.02%~0.04%, ensuring sufficient grain refinement while avoiding excessive addition that could form large inclusions that impair the plasticity and fatigue properties of the wire rod.
[0016] 6. Boron (B): Even in trace amounts, boron preferentially segregates at austenite grain boundaries, filling vacancies and defects, and blocking the channels for rapid carbon diffusion along grain boundaries, thereby inhibiting decarburization at the grain boundary level. Simultaneously, B significantly improves the hardenability of steel, ensuring the core properties of large-diameter wire rods after heat treatment. The grain boundary segregation of B also synergistically enhances the effect of V grain refinement: V grain refinement increases the grain boundary area, providing more segregation sites for B and improving its segregation efficiency; conversely, B segregation inhibits the coarsening tendency of V carbides at grain boundaries, creating a mutually reinforcing "double barrier effect." This invention controls the B content to 0.0005%~0.0015%, within which the effect of grain boundary segregation in inhibiting decarburization and improving hardenability is fully utilized, while avoiding the formation of coarse precipitates from excessive B that could impair toughness. Furthermore, the weight percentage ratio of V to B is controlled between 15 and 80 to ensure optimal synergistic matching between the two at both the intragranular and grain boundary levels.
[0017] 7. P, S: Phosphorus and sulfur are considered harmful elements in this steel grade. Phosphorus easily segregates at grain boundaries, causing cold brittleness and reducing the low-temperature toughness and fatigue resistance of the wire rod; sulfur easily forms sulfide inclusions, causing hot brittleness, worsening the drawing and heat treatment conditions of the steel wire, and reducing the fatigue life of the spring. Therefore, their content needs to be controlled at a low level. This invention controls P ≤ 0.015% and S ≤ 0.010% to ensure the purity and processing performance of the wire rod.
[0018] In summary, this invention ensures the basic mechanical properties and hardenability of the wire rod through the use of C, Si, Mn, and Cr. Based on this, trace amounts of V and B are added, utilizing the grain refinement of V and the grain boundary segregation of B to form a synergistic "double barrier effect," inhibiting the diffusion and migration of carbon atoms from both intragranular and grain boundary dimensions, thereby effectively reducing the decarburization sensitivity of 55SiCr spring steel. Simultaneously, the content of harmful elements such as P and S is strictly controlled to ensure the purity of the wire rod. The selection of the content range of each element ensures both the mechanical properties of the wire rod and the effective control of the decarburized layer.
[0019] The microstructure of the aforementioned spring steel wire rod consists of fine lamellar pearlite and ferrite, with the ferrite volume percentage ranging from 5% to 15% and a grain size of 10 to 12. The total decarburized layer depth is 0, and the total decarburized layer depth is ≤0.5%D, where D is the wire rod diameter. The specifications of the spring steel wire rod are Φ5.0mm to Φ25.0mm. The tensile strength of the spring steel wire rod is 950 to 1150 MPa.
[0020] A method for producing VB composite microalloyed spring steel wire rod with a completely decarburized layer includes the following steps: 1) Heating: Heat the steel billet to 950~1050℃, keep it warm after it is heated evenly, and control the air-fuel ratio in the heating furnace to 1.3~1.9.
[0021] 2) Rolling: The heated steel billet is subjected to finish rolling and double-module rolling in sequence. The temperature of entering the finish rolling is 850~920℃, and the temperature of exiting the wire is 850~900℃.
[0022] 3) Cooling: After spinning, cool to below 700℃ at a cooling rate of 3~8℃ / s, then cool to below 600℃ at a cooling rate of 1~3℃ / s, and then wind up.
[0023] Furthermore, in step 1), the total furnace time is 90~120 min.
[0024] Furthermore, in step 1), the heat spread temperature is 1000~1080℃.
[0025] Furthermore, in step 1), the calorific value of the heating furnace atmosphere is ≥2000 kJ / m³. 3 .
[0026] Furthermore, in step 2), the temperature of the dual-module input is 850~900℃.
[0027] Compared with the prior art, the beneficial effects of the present invention are: 1. The synergistic effect of component design and process control enabled effective control of the decarburization layer. The grain refinement effect of volatile organic compounds (V) and the grain boundary segregation effect of carbon (B) construct a "double barrier" at the microscopic level to inhibit carbon atom diffusion. V reduces the driving force for carbon atom migration to the surface by refining austenite grains and lowering the diffusion coefficient of carbon in austenite. B preferentially segregates at austenite grain boundaries, blocking the rapid diffusion channels of carbon along the grain boundaries and thus blocking the path of carbon atom migration to the surface. At the same time, the matching heating process ensures that the residence time of the billet in the high-temperature range is effectively controlled, and the weakly oxidizing furnace atmosphere (air-fuel ratio 1.3~1.9) reduces the thermodynamic driving force for surface oxidation and decarburization of the billet. The temperature regime of finishing rolling and bi-module rolling ensures that the austenite grains are continuously refined during deformation, so that the grain refinement effect of V can be fully utilized. The two-stage cooling regime after wire drawing (rapid cooling at 3~8℃ / s to below 700℃, and then cooling at 1~3℃ / s to below 600℃) inhibits the continued expansion of the decarburized layer in the high-temperature stage. The synergistic design of components and processes enables the wire rod to achieve a total decarburization layer depth of 0 without the need for peeling or spraying anti-decarburization coating, with the total decarburization layer depth controlled at 0.3%~0.5%D (Examples 1~8). This represents a significant improvement compared to the conventional process where the total decarburization layer is ≤1.5%D.
[0028] 2. The compositional design of VB composite microalloying reduces the decarburization sensitivity of wire rods. This invention, based on the standard 55SiCr composition system, incorporates 0.02%–0.04% V and 0.0005%–0.0015% B, with the V / B weight percentage controlled between 15 and 80. V refines austenite grains by forming fine carbonitrides that pin grain boundaries, increasing the total grain boundary area and reducing the diffusion flux of carbon along grain boundaries. B segregates at austenite grain boundaries, filling vacancies and defects, and blocking the rapid diffusion channels of carbon along grain boundaries. The grain-refining effect of V creates more effective grain boundary area for B grain boundary segregation, improving B segregation efficiency; conversely, B grain boundary segregation inhibits the coarsening tendency of V carbides at grain boundaries, forming a mutually reinforcing synergistic mechanism. This composition design reduces the driving force for carbon atom migration to the surface at the intrinsic material level, achieving an effective reduction in decarburization sensitivity without relying on additional processes such as coating protection or peeling.
[0029] 3. Optimized process control suppressed the spread of decarburization during heating and rolling. In the heating process, the heating temperature is 950~1050℃, the soaking temperature is 1000~1080℃, and the total furnace time is 90~120min. Combined with a weakly oxidizing atmosphere and an air-fuel ratio of 1.3~1.9, this ensures that the carbonitrides of V are fully dissolved to exert the grain refinement effect and that B is evenly distributed to ensure the grain boundary segregation effect. At the same time, it avoids severe decarburization caused by excessively high temperatures and excessively long furnace times. In the rolling process, the temperature regime of 850~920℃ for entering the finishing mill, 850~900℃ for entering the double-module, and 850~900℃ for wire drawing is matched with the precipitation temperature window of V. This promotes dynamic recrystallization and grain refinement during finishing milling and double-module deformation, allowing the grain refinement effect of V to continue to play a role during deformation. The two-stage cooling process—rapidly cooling the wire rod to below 700℃ at 3~8℃ / s after winding, and then further cooling it to below 600℃ at 1~3℃ / s—shortens the residence time of the wire rod in the high-temperature zone and inhibits the continued expansion of the decarburized layer during the cooling stage after winding. The combined effect of the above process control reduces the total decarburized layer depth of the wire rod to 0, and controls the total decarburized layer depth to below 0.5%D.
[0030] 4. The synergistic combination of components and processes resulted in a uniform and refined microstructure. Through the synergistic effect of VB composite microalloying grain refinement and the matching heating-rolling-cooling process, the wire rod of this invention achieves a uniform and refined microstructure. The carbonitride precipitates of VB pin grain boundaries, while the grain boundary segregation of VB inhibits grain boundary migration. These two elements work together to suppress austenite grain growth. Combined with dynamic recrystallization refinement during rolling and two-stage cooling after wire drawing, the wire rod's microstructure forms a multiphase structure of fine lamellar pearlite + 5%~15% ferrite, with a grain size reaching 10~12. The refined grains and uniform microstructure ensure the uniformity of the wire rod's cross-sectional structure, providing an organizational basis for achieving stable mechanical properties and excellent drawing performance.
[0031] In summary, through the synergistic effect of the above-mentioned component design and process control, the tensile strength of the wire rod of this invention reaches 980~1150MPa (Examples 1~8), maintaining stability and slightly improving upon the tensile strength level of 950~1150MPa achieved by conventional processes. More importantly, the total decarburization layer depth of the wire rod is 0, and the total decarburization layer depth is controlled at 0.3%~0.5%D (D is the wire rod diameter), achieving a reduction of more than 50% compared to the total decarburization layer of ≤1.5%D in conventional processes. The complete elimination of the decarburization layer and the significant reduction in the total decarburization layer effectively avoid the decrease in surface hardness and the formation of fatigue crack initiation caused by the decarburization layer, significantly improving the surface quality of the wire rod and its subsequent drawing performance, ensuring the fatigue life and safety of the spring during service. At the same time, it does not require additional processes or special equipment such as peeling treatment or coating protection, and is suitable for the stable industrial production of 55SiCr spring steel wire rods with a specification range of Φ5.0mm~Φ25.0mm. Attached Figure Description
[0032] Figure 1 This is a metallographic photograph of the decarburized layer of 55SiCr spring steel wire rod produced in Embodiment 5 of the present invention with a diameter of 16mm.
[0033] Figure 2 This is a metallographic photograph of the decarburized layer of 55SiCr spring steel wire rod produced using conventional processes (comparative example) for 16mm specification. Detailed Implementation
[0034] This invention discloses a VB composite microalloyed spring steel wire rod with a completely decarburized layer and its production method. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the same result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments, and those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0035] The production process of the wire rod of this invention includes heating, rolling, and cooling of the continuously cast billet. A two-stage cooling control is used after the wire rod is produced. This invention is applicable to the production of spring steel wire rods with diameters from Φ5.0mm to Φ25.0mm. The specific production process of each embodiment includes the following steps: 1) Heating: Heat the continuously cast billet to 950~1050℃, then homogenize it to 1000~1080℃, with a total furnace time of 90~120min. The furnace atmosphere should be controlled with a weak oxidizing atmosphere and a calorific value ≥2000kJ / m³. 3 The air-fuel ratio inside the heating furnace is controlled at 1.3~1.9.
[0036] 2) Wire rod rolling: The heated continuous casting billet is subjected to finish rolling and double-module rolling in sequence. The temperature of entering the finish rolling is 850~920℃, the temperature of entering the double module is 850~900℃, and the temperature of wire exiting is 850~900℃.
[0037] 3) Wire rod cooling: After spinning, cool to below 700℃ at a cooling rate of 3~8℃ / s, then cool to below 600℃ at a cooling rate of 1~3℃ / s, and then coil.
[0038] The chemical composition of the comparative examples and embodiments of this invention is shown in Table 1, the heating process parameters are shown in Table 2, the rolling process parameters are shown in Table 3, and the decarburization layer index and mechanical properties are shown in Table 4. Each embodiment uses the comparative example as a reference standard. The comparative example is a conventional 55SiCr spring steel wire rod (without added V and B), produced using conventional heating, rolling, and cooling processes.
[0039] Table 1 Chemical composition (wt%) of the comparative examples and embodiments of the present invention
[0040] Table 2 Heating process parameters of the comparative examples and embodiments of the present invention
[0041] Table 3 Rolling process parameters of the comparative examples and embodiments of the present invention
[0042] Table 4. Decarburization layer properties and mechanical properties of the comparative examples and embodiments of the present invention.
[0043] As shown in Table 4, using Examples 1-8 of the present invention, the tensile strength of the wire rod reaches 980-1150 MPa, the total decarburization layer depth is 0, and the total decarburization layer depth is controlled at 0.3%-0.5%D. In contrast, the total decarburization layer depth of the conventional process (comparative example) is 1.4%D, and there is a total decarburization layer below 30 μm. The total decarburization layer depth of the wire rod in each embodiment of the present invention is reduced by more than 50% compared with the conventional process (comparative example), achieving a significant decarburization control effect.
[0044] Metallographic analysis of the wire rods showed that the microstructure of the wire rods in all embodiments of the present invention consisted of fine lamellar pearlite and ferrite, with the ferrite volume percentage ranging from 5% to 15% and the grain size from 10 to 12. The refined grains and uniform microstructure ensured the uniformity of the wire rod cross-section microstructure. Figure 2 Metallographic photograph of the decarburized layer of 55SiCr spring steel wire rod produced using conventional processes (comparative example) for 16mm gauge. Figure 1 Metallographic photograph of the decarburized layer of 55SiCr spring steel wire rod produced in Example 5 of this invention (16mm specification). Figure 1 and Figure 2 As can be seen from the comparison, the surface of the wire rod produced by conventional process (comparative example) has an obvious decarburized layer, while the surface of the wire rod produced by the present invention has no decarburized layer, and the total decarburized layer depth is significantly reduced.
[0045] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A VB composite microalloyed spring steel wire rod with a completely decarburized layer eliminated, characterized in that, Composed of the following chemical components in weight percentage composition: C: 0.51%~0.59%, Si: 1.30%~1.50%, Mn: 0.60%~0.80%, P≤0.015%, S≤0.010%, Cr: 0.60%~0.75%, V: 0.02%~0.04%, B: 0.0005%~0.0015%, and the weight percentage ratio of V / B is 15~80, with the balance being Fe and unavoidable impurities; The microstructure of the spring steel wire rod is fine lamellar pearlite + ferrite, wherein the volume percentage of ferrite is 5%~15% and the grain size is 10~12. Furthermore, the total decarburization layer depth of the spring steel wire rod is 0, and the total decarburization layer depth is ≤0.5%D, where D is the wire rod diameter.
2. The VB composite microalloyed spring steel wire rod with eliminated decarburized layer according to claim 1, characterized in that, The specifications of the spring steel wire rod are Φ5.0mm~Φ25.0mm.
3. The VB composite microalloyed spring steel wire rod with eliminated decarburized layer according to claim 1, characterized in that, The tensile strength of the spring steel wire rod is 950~1150MPa.
4. The production method of VB composite microalloyed spring steel wire rod with the complete decarburization layer as described in any one of claims 1 to 3, characterized in that, Includes the following steps: 1) Heating: Heat the steel billet to 950~1050℃, keep it at that temperature after it has been heated evenly, and control the air-fuel ratio in the heating furnace to 1.3~1.9; 2) Rolling: The heated steel billet is subjected to finish rolling and double-module rolling in sequence. The entry temperature of the finish rolling is 850~920℃, and the exit temperature is 850~900℃. 3) Cooling: After spinning, cool to below 700℃ at a cooling rate of 3~8℃ / s, then cool to below 600℃ at a cooling rate of 1~3℃ / s, and then wind up.
5. The method for producing VB composite microalloyed spring steel wire rod with a completely decarburized layer according to claim 4, characterized in that, In step 1), the total furnace time is 90~120 minutes.
6. The method for producing VB composite microalloyed spring steel wire rod with a completely decarburized layer according to claim 4, characterized in that, In step 1), the heat spreader temperature is 1000~1080℃.
7. The method for producing VB composite microalloyed spring steel wire rod with a completely decarburized layer according to claim 4, characterized in that, In step 1), the calorific value of the heating furnace atmosphere is ≥2000 kJ / m³. 3 .
8. The method for producing VB composite microalloyed spring steel wire rod with a completely decarburized layer according to claim 4, characterized in that, In step 2), the temperature of the dual-module input is 850~900℃.
Citation Information
Patent Citations
Production method for eliminating full decarburization of Si-Cr series spring steel wire rod and prolonging fatigue life
CN115870332A
Full decarburization control process for automobile spring steel 55SiCr wire rod
CN116445698A
High utilization stress spring steel for automobile
CN1279204C